El Sacro Imperio Romano, el emperador de los últimos tiempos y el katechon = Abweichender Titel: The Holy Roman Empire, the Emperor of the Last Days and the Katechon - Rodríguez de la Peña, Manuel Alejandro (Cauriensia, 2025)
The medieval myth of the Emperor of the Last Days, closely linked conceptually with the Pauline archetype of the Katechon, played an important role in the propaganda narratives and political prophecy of the Holy Roman Empire from the mid-twelfth century onwards. Specifically, the political theology of the Christian universal monarchy as the heir of Rome was linked to the eschatology of the Katechon. In this essay we will address three moments in which the myth of the Emperor of the Last Days played a prominent role in the imperial discourse: the period of the Hohenstaufen, the Roman revolution of Cola di Rienzo and the time of the first Habsburgs.